Verbal protocol: concurrent verbalization and retrospective - Lacerda Mattos, Thais Caroline [UNESP]; Redigolo, Franciele Marques [UNESP]; Brito Neves, Dulce Amelia de; Lopes Fujita, Mariangela Spotti [UNESP] (Univ Brasilia, Dept Ciencia Informacao, 2017)
The problem regarding the validity of the application of the Verbal Protocol method, and more specifically on the theoretical and empirical evidence notes that possible failures and inconsistencies that this method may present the research that aims to reflect on the two verbalizations related to the technique of the Verbal Protocol's qualitative analysis. In this technique, there are two approaches that offer different possibilities for research. The first one is the concurrent verbalization, which is to perform a job while the verbal report and the second one is the retrospective verbalization what happens after the job is executed. Each of them is subject to criticism as to its possible reactivity and non veridicality, thence our reflection on its possibilities and limits. From review of a literature revealed that, despite the prevailing theory give more support to the verbalization competitor technique, some authors, based on empirical tests, pointed out some advantages of hindsight technique, and even, the equated in terms of quality to the competing technical. The verbal protocol proves to be very effective for understanding the cognitive processes related to a research by attendance that seeks to understand the context of the social actor's work through capitation of the verbalizations that complements the formal data collection and information.
Keywords: Cognitive Process; Retrospective Verbalization; Verbal Protocol; Concurrent Verbalization